Analisis Pengaruh Penggunaan Quizizz dalam Mengefektifkan Pemberian Soal dan Kuis pada Siswa Melalui Media Digital di SD Pekayon 09 - Salwa, Netha Salwa Noviyanti; Frisian Nur Hanapiah; Intan Ratu Anggia; Rhaudya Zihan Esa Maghfira; Tin Rustini (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the effectiveness of using Quizizz as a digital learning evaluation media at SD Pekayon 09. Using a qualitative approach with a case study method, this study explores teachers' experiences in designing and implementing Quizizz in the evaluation process. The research subjects were selected through purposive sampling techniques, namely one class teacher who actively uses Quizizz in learning evaluation activities. Data were collected through in-depth interviews and observations of learning videos, both online and offline. Data analysis was carried out using a thematic analysis approach according to Braun and Clarke (2006), which consists of six systematic stages in identifying key themes from qualitative data. The results of the study showed that Quizizz was able to increase student engagement through gamification features, accelerate the assessment process, and provide instant feedback that helps students' understanding. However, challenges such as limited technological infrastructure and student adaptation to digital devices are still obstacles. Thus, Quizizz has the potential to be an innovative solution in increasing the effectiveness of learning evaluation at the Elementary School level, with adequate training and infrastructure support.